Magnesium-catalyzed CO2 reduction to formic acid or methanol: solvent or no solvent settles the selectivity - Mahata, Biplab; Khilari, Nripen; Koley, Debasis; Sen, Sakya S. (Inorganic Chemistry, 2026)
Reducing the carbonyl (C=O) group in carbon dioxide is a difficult yet crucial step for producing valuable chemical compounds. This approach holds promise for creating new methods to utilize nonfossil-based raw materials. Using catalysts made from abundant, inexpensive, and environmentally friendly metals, such as magnesium, could significantly advance the development of sustainable synthetic techniques. In this study, a magnesium pincer compound (1) is shown to facilitate the reduction of CO2 with pinacolborane as the reductant. When used without a solvent, the reaction produces methoxyborane, whereas in THF, it leads to formoxyborane. Formoxyborane has been identified as a ``missing link'' in homogeneous CO2 reduction by catalysts based on alkaline earth metal elements. The variation in product selectivity was substantiated through DFT calculations. The initial generation of the Mg(II) hydride catalyst both in the absence and presence of THF entails an activation barrier within 25-26 kcal mol-1. However, the rate-determining step, in the absence of a solvent, involves hydride transfer-mediated reduction at the formate fragment accompanying a transition barrier of 27.3 kcal mol-1. In the presence of THF, the rate-determining step involves hydride transfer to the Mg center with a barrier of 29.2 kcal mol-1, generating the catalyst and boryl formate.